Analysis of Price, Promotion and Product Quality on Consumer Satisfaction at Donat Kak Ita MSMEs Medan - Almira, Fadilla; S.Sos., M.I.Kom, Dina Octavia (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
The purpose of this study was to determine the effect of product quality, price, and promotion on consumer purchasing interest in Donat Kak Ita MSMEs Medan. The analysis used is associative analysis, this research method is quantitative. The population in this study were consumers who visited the Donat Kak Ita MSMEs Medan with an average of 70 visitors, and this study was conducted for 2 weeks or 14 days so that the population in this study was 980 people. The sampling method in this study used the Nonprobability Sampling method with the Accidental Sampling technique. So the sample using the Slovin formula in this study amounted to 91 respondents. The results obtained from this study indicate that: 1) Price has a partial and significant effect on Purchase Intention, 2) Promotion partially and significantly affects Purchase Intention, 3) Product quality has a partial and significant effect on Purchase Intention, 4) Product Quality , Price, and Promotion simultaneously and significantly influence purchasing interest. The adjusted R square value of 0.399 can be called the coefficient of determination, this means 0.399 (39.9%) Buying Interest can be obtained and explained by Product Quality, Price, and Promotion while the remaining 60.1% is explained by variables outside the model that are not studied .